(3ebheGJ GdJcdjas - (3GdfGHdSj, eMeO QGJHs ((3GdCQOf (B[(3YeGf(B]s (3eDSSI GdaQSGf ddfTQ hGdJhRjYs, 2013)
(3GdYHGOI WGYI WhYjI, eeRhLI HeMHI bdHjI, CSGSgG eYQaI jbjfjI JaVj Edi SYGOI CHOjI(B. (3hgPG GdcJGH jJUd HGdLGfH GdeYQaj ef GdYHGOI, dcfg jJfGhd GdYbjOI ef RGhjI LOjOI, aGdEfSGf gh GdeNdhb GdChd QJHI, hGdecQe JaVdG, hGdecda HYHGOI QHg hJRcjI faSg egeI; dJchf gPg GdJRcjI KefG dJdce GdLfI, dgPG efM Gddg GdEfSGf ebheGJ gPg GdJRcjI; chfG eSNQG JSNjQ JYQja hJcQje, hYbdG gh COGI GdeYQaI hefGW GdJcdja, haWQI JcTa ddEfSGf NWCg hGfMQGag, hTghI jQbi GdEfSGf HgG UGHQG hTGcQG, hMQjI GNJjGQ JKef GdYed hJbj GdRdd, RefgLG jUMM GdeSGQ, cd gPG Ydi eSQM ecGfj gh GdCQV, haj XQa ReGfj gh GdYeQ(B. (3hGdcJGH jWQM Jdc GdebheGJ HCSdhH Sgd eHSW, hjbQH CacGQg Edi GdCPgGf Yf WQjb GdQHW HGdhGbY hVQH GdeKd, gh jfGSH LejY GdTQGFM hjgOa Edi EQSGA dHfI aj HfGA GdYbjOI GdSdjeI GdeSJbGI ef cJGH Gddg JYGdi hSfI QShdg Udi Gddg Ydjg hSdes
11
Keywords: (3GdKbGaI GdESdGejIs; (3GdMOjKs -- (3LeY hJOhjfs; (3GdbQCfs -- (3JQLeI GdEfLdjRjIs; (3GdbQCfs -- (3JaSjQs; (3UMjM GdHNGQjs